TECNOLOGIA E PSICOLOGIA: uma análise da percepção de psicólogos clínicos maranhenses sobre o uso das Tecnologias da Informação e Comunicação (TICS). - DINIZ, Thaís Carvalho Ferreira (2021)
The field of new technologies has grown rapidly in recent years, affecting several areas such as the economy, politics, education and health. And Information and Communication Technologies (ICTs) are inserted in this context, with their application both in the organizational scope and for domestic use. The world is in constant technological transformation, we are currently living in an era called the Society or Economy of Information and Knowledge. Changes begin to be noticed in practically all areas of work and it would not be different with Psychology. In order to investigate this repercussion, we sought to analyze how ICTs are used and perceived in the context of clinical psychologists from Maranhão. This study is characterized as exploratory and through qualitative analysis it discussed a current panorama of new information and communication technologies and technologies (tics) and their relationship with psychology through a theoretical framework based on the theme and through semi-structured interviews with ten clinical psychologists from Maranhão. Despite the interviewees being from different psychological theoretical approaches, some similar perceptions were presented, but also divergences. Regarding the use of new technologies and information and communication technologies (tics) by psychologists from Maranhão, it was obtained as a result that most professionals use some technological tool such as devices, applications or other resources, online therapy was highlighted, adopted in the context of the Covid-19 pandemic by all psychologists. And regarding the psychologists' perception of the use of Information and Communication Technologies (ICTs) and technological resources in the context of clinical work, ICTs were considered as a great facilitator for the professional. Most psychologists use these resources, identifying their adaptations to technological changes, and the need to train these professionals in order to manage and update their therapeutic interventions is also emphasized.